محن الجزائر في عهد الداي عمر 1815-1817م ومواقفه منها - عطية, محمد (جامعة الوادي - University of Eloued, 2017)
يعد القرن التاسع عشر ميلادي من أدق و اخطر مراحل الحكم العثماني في الجزائر، و لعل عهد الداي عمر واحدا من تلك العهود التي توالت فيها المحن على الايالة التي كانت تسترد أنفاسها و اعظم المخاطر التي واجهها الداي ذلك التكالب الصليبي للنيل من سيادة الجزائر و انهاء سيطرتها التي فاقت قرون من الزمن على الحوض الغربي للمتوسط، و كشفت العدو من الصديق فالمساندة العثمانية و الطرابلسية و حتى المغربية كانت حاضرة. The nineteenth century is considered to be one of the most accurate and dangerous stages during the Ottoman Era in Algeria. Dey Omar's Era is one of them where the Regency suffered from many adversities while it was recovering its breath. the greatest danger that Regency faced was the Crusader Aggression to undermine Algeria's sovereign and make an end to its domination in the Western Mediterranean that lasted for centuries. These events revealed friend from foe, Algeria gained support from Ottomans,Tripoli, as well as Morocco.
مقال
Keywords: محن الجزائر - الداي عمر